The state of scientific research of militia activity in Ukraine during the period of partial liberalisation of the political regime in the USSR (1953–1962) - V. A. Grechenko; O. N. Yarmysh (Law and Safety)
The historiography of militia activity during the years of partial de-Stalinisation is divided into two stages: the Soviet period and the period of Ukraine’s independence. The 1960s-1980s were marked by a significant increase in researchers' interest in studying the general issues of the history and legal foundations of internal affairs. At that time, monographic studies and dissertations appeared, which dealt with various issues of theory and practice of organisation and functioning of militia bodies, including development and improvement of the structure, functions and legal basis of their activities, restructuring of the work of internal affairs bodies in accordance with the conditions of the “thaw”, organisation of combating crime, protection of public order, performance of managerial and economic tasks, and resolution of special issues. A significant part of the works covers the issues of party leadership of internal affairs bodies, they are presented exclusively within the framework of the traditional assessment of the activities of these institutions, i.e. their “praise and glorification”.